Effect of surface roughness of solid particles on the regimes and outcomes of their collisions with liquid droplets; Experimental Thermal and Fluid Science; Vol. 142 - Islamova A. G. Anastasiya Gomilievna; Tkachenko P. P. Pavel Petrovich; Shlegel N. E. Nikita Evgenjevich; Strizhak P. A. Pavel Alexandrovich (2023, 2023)
Title screen